Risk Factors and Outcomes of Recurrent Candidemia in Children: Relapse or Re-Infection? - Lai, Mei-Yin (J Clin Med, 2019)
In this paper, our aim was to investigate the incidence, clinical characteristics, risk factors, and outcomes of recurrent candidemia in children. We retrospectively reviewed all children with candidemia from a medical center in Taiwan between 2004 and 2015. Two episodes of candidemia ≥30 days apart with clinical and microbiological resolution in the interim were defined as “late recurrence”, and those that had 8–29 days apart from previous episodes were defined as “early recurrence”. 45 patients (17.2%) had 57 episodes of recurrent candidemia, and 24 had 28 episodes of late recurrent candidemia. The median time between recurrences was 1.8 months (range: <1 month to 13 months). Of those, 29 had relapsed candidemia and 28 were re-infected by different Candida species (n = 24) or by different strains (n = 4). Recurrent candidemia patients were more likely to require echinocandins treatment, had a longer duration of candidemia, and higher rate of treatment failure (p = 0.001, 0.014, and 0.012, respectively). Underlying gastrointestinal diseases (Odds ratio (OR) 3.84; 95% Confidence interval (CI) 1.81–8.12) and neurological sequelae (OR 2.32; 95% CI 1.15–4.69) were independently associated with the development of recurrent candidemia. 17.2% of pediatric patients with candidemia developed recurrent candidemia, and approximately half were re-infected. Underlying gastrointestinal diseases and neurological sequelae were the independent risk factors for recurrent candidemia.